Belief Adjustment Model with self-review debiaser presentation patterns on investment decision making - Antiqueain Maliu; Luciana Spica Almilia; Putri Wulanditya (University of Merdeka Malang, 2020)
This study aims to examine and find out the influence of related variables, namely evidence sequence (good news followed by bad news and bad news followed by good news) and information series (long and short information) on the self-review debiaser presentation pattern based on accounting information for investment decision making. The experimental design used in this study is a 2 x 2 mixed design factorial experimental design (between subject and within subject) that manipulates the independent variable evidence sequence (good news followed by bad news and bad news followed by good news) and information series (long and short) on the Self-review debiaser presentation pattern. Participants in this study were 124 S1 Accounting Students of STIE Perbanas Surabaya. This study used the normality test and the Mann Whitney Test. The overall results of the hypothesis are partially held. The results of this study indicate that the self-review debiaser presentation pattern is proven to reduce the effect of sequences on long information series. However, self-review debiaser presentation pattern has proven unable to reduce the effect of sequence or no order effet on short information series.JEL Classification: G32, G34, M41DOI: https://doi.org/10.26905/jkdp.v24i3.4097